2023
DOI: 10.3389/fimmu.2023.1167917
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 and non-COVID-19 severe sepsis converge transcriptionally after a week in the intensive care unit, indicating common disease mechanisms

Abstract: IntroductionSevere COVID-19 and non-COVID-19 pulmonary sepsis share pathophysiological, immunological, and clinical features. To what extent they share mechanistically-based gene expression trajectories throughout hospitalization was unknown. Our objective was to compare gene expression trajectories between severe COVID-19 patients and contemporaneous non-COVID-19 severe sepsis patients in the intensive care unit (ICU).MethodsIn this prospective single-center observational cohort study, whole blood was drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…This persistent immune dysfunction involved both inflammatory and immunosuppressive components ( Figures 1C , 2 , 3A ), as observed in both COVID-19 and non-COVID-19 sepsis non-survivors ( Figure S2C, D ) and in external datasets of COVID-19 and sepsis patients ( Figure S4 ). While differences in the early antiviral response existed between these two groups ( Figures S2B, S9 ), consistent with our previous work ( 11 ), overall, the underlying persistent immune dysfunction involved in mortality was highly conserved in both COVID-19 and non-COVID-19 sepsis ( Figure S2D ). The connection between persistence and mortality was further supported by persistent enrichment of our published mortality signature ( Figure 4A ) and the results from the endotype analysis, where most non-survivors remained associated with the high severity endotypes NPS and INF throughout disease ( Figure 4C ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This persistent immune dysfunction involved both inflammatory and immunosuppressive components ( Figures 1C , 2 , 3A ), as observed in both COVID-19 and non-COVID-19 sepsis non-survivors ( Figure S2C, D ) and in external datasets of COVID-19 and sepsis patients ( Figure S4 ). While differences in the early antiviral response existed between these two groups ( Figures S2B, S9 ), consistent with our previous work ( 11 ), overall, the underlying persistent immune dysfunction involved in mortality was highly conserved in both COVID-19 and non-COVID-19 sepsis ( Figure S2D ). The connection between persistence and mortality was further supported by persistent enrichment of our published mortality signature ( Figure 4A ) and the results from the endotype analysis, where most non-survivors remained associated with the high severity endotypes NPS and INF throughout disease ( Figure 4C ).…”
Section: Discussionsupporting
confidence: 90%
“…Whole blood from 5 healthy controls from Vancouver, Canada were processed alongside the patient samples. Further details on study design and RNA-Seq methodology can be found in our previously published protocol ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The down-regulation of these immune pathways suggested a decrease in the activity of multiple inflammatory processes, which was further supported by the upregulation over time of the anti-inflammatory pathway “Interleukin-10 signaling” ( Figure 1C ). In particular, these hemostasis and inflammatory pathways have been shown in the literature to be largely upregulated in hospitalised COVID-19 patients ( 50 52 ). Thus, the observed down-regulation over time may suggest a return to homeostasis after discharge in only patients who did not have post-COVID symptoms at follow-up.…”
Section: Resultsmentioning
confidence: 99%